Instructional level moderation at improving numerical literacy skills through creative problem-solving learning models - Apriatni, Sri; Nindiasari, Hepsi; Sukirwan, Sukirwan; Khaeroni, Khaeroni (Universitas Islam Raden Intan Lampung, INDONESIA, 2023)
Background: In today's ever-changing landscape, students need strong numerical literacy skills to navigate life's complexities. Recognizing that students come with various learning capabilities, often referred to as